2013
DOI: 10.1007/s11524-013-9810-2
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Tobacco Retail Outlets and Smoking Initiation among New York City Adolescents

Abstract: This study was designed to estimate the relationship between exposure to tobacco retail outlets and smoking initiation in a racially diverse urban setting. Using data from the 2011 NYC Youth Risk Behavior Survey, multivariable logistic regression analyses were conducted to estimate the exposure-initiation relationship and test for effect modification, while controlling for covariates. The predicted probability of smoking initiation from the multivariable model increased from 7.7 % for zero times a week exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 27 publications
1
35
0
1
Order By: Relevance
“…That is, lifetime smoking by adolescents was greater in cities with higher outlet density. This is also consistent with results of another study which found that adolescents who visited tobacco outlets two or more times per week had greater odds of smoking initiation (36). Our results also showed that tobacco outlet density was related to youths’ tobacco beliefs, such that greater density was associated with greater perceived cigarette availability and with lower perceived enforcement of underage tobacco policies.…”
Section: Discussionsupporting
confidence: 92%
“…That is, lifetime smoking by adolescents was greater in cities with higher outlet density. This is also consistent with results of another study which found that adolescents who visited tobacco outlets two or more times per week had greater odds of smoking initiation (36). Our results also showed that tobacco outlet density was related to youths’ tobacco beliefs, such that greater density was associated with greater perceived cigarette availability and with lower perceived enforcement of underage tobacco policies.…”
Section: Discussionsupporting
confidence: 92%
“…Several potentially relevant articles identified during the literature search process did not meet inclusion criteria, including a study with a college student sample;11 studies using an exposure measure that included but was not specific to POS marketing;12 13 studies assessing the relationship between smoking and exposure to tobacco advertising in general,14 and studies investigating access to tobacco retailers and smoking 15 16…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it is not uncommon for middle-aged Americans to experience job instability (US Bureau of Labor Statistics, 2010) and job loss (Dupre, George, Liu, & Peterson, 2012) during this stage of life, which can be concerning when considering the linkages between stress, poverty, and smoking that have been documented (Perettti-Watel & Constance, 2009; Shuaib et al, 2011). Given the socioeconomic challenges faced by many middle-aged Americans, coupled with the potential for increased exposure to environmental cues to smoke such as high concentrations of tobacco outlets (Peterson et al, 2011; Rodriguez, Carlos, Adachi-Mejia, Berke, & Sargent, 2012; Yu, Peterson, Sheffer, Reidm, & Schnieder, 2010) and tobacco advertising (Johns, Sacks, Rane, & Kansagra, 2013) in urban settings, identifying factors that protect against tobacco use among urban middle-aged persons is warranted. The purpose of the current study is to examine the influence of religious attendance on smoking status over time among a diverse sample of middle-aged lifetime smokers who reside in an urban setting.…”
Section: Introductionmentioning
confidence: 99%